2020
DOI: 10.1101/2020.12.19.423584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of NPC1 as a novel SARS-CoV-2 intracellular target

Abstract: Niemann-Pick type C1 (NPC1) receptor is an endosomal membrane protein that regulates intracellular cholesterol trafficking, which is crucial in the Ebola virus (EBOV) cycle. The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) enters the cell by binding of the viral spike (S) protein to the ACE2 receptor. This requires S-protein processing either by the surface transmembrane serine protease TMPRSS2 for plasma membrane fusion or cathepsin L for endosomal entry. Additional host factors are required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Further elucidation of the latter and how it is modulated by viruses thus presents as important aspect of focus. After cholesterol-dependent steps in endocytosis, shuttling of the lipid within virus-containing endosomes further is important for the uncoating, and therefore for final cellular entry, of enveloped viruses, such as members of the Filoviridae family, IAV, HIV, SARS-CoV-2, and Alphaviruses ( Schroeder, 2010 ; Carette et al, 2011 ; Côté et al, 2011 ; Garcia-Dorival et al, 2020 ; Martyna et al, 2020 ; Sousa et al, 2020 ). This process is reported to be mediated via cholesterol-shuttling proteins, such as NPC1.…”
Section: Endosomal Cholesterol Trafficking As Shared Feature In Viral Infectionsmentioning
confidence: 99%
“…Further elucidation of the latter and how it is modulated by viruses thus presents as important aspect of focus. After cholesterol-dependent steps in endocytosis, shuttling of the lipid within virus-containing endosomes further is important for the uncoating, and therefore for final cellular entry, of enveloped viruses, such as members of the Filoviridae family, IAV, HIV, SARS-CoV-2, and Alphaviruses ( Schroeder, 2010 ; Carette et al, 2011 ; Côté et al, 2011 ; Garcia-Dorival et al, 2020 ; Martyna et al, 2020 ; Sousa et al, 2020 ). This process is reported to be mediated via cholesterol-shuttling proteins, such as NPC1.…”
Section: Endosomal Cholesterol Trafficking As Shared Feature In Viral Infectionsmentioning
confidence: 99%
“…Recently, a positive interaction between NPC1 and SARS-CoV-2 Nucleoprotein was reported (22). Consequently, NPC1 appears to be relevant in a variety of RNA or DNA viral families.…”
Section: Discussionmentioning
confidence: 99%
“…These compounds act either by binding to NPC1 sterol sensing domain (SSD) or by blocking EBOV Glycoprotein (GP) GP-NPC1 interaction, respectively. This indicates that NPC1 and intact cholesterol transport are pivotal for a successful infection (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
mentioning
confidence: 99%
“…82,83 A recent study identified an interaction between SARS-CoV-2 nucleoprotein and NPC1, suggesting NPC1 to be a facilitator for the endocytosis of SARS-CoV-2. 26 U18666A, an inhibitor of NPC1, 84 significantly inhibited the infection and replication of SARS-CoV-2 in Vero E6 and Calu-3 cells. 27 This anti-SARS-CoV-2 activity was associated with increased cholesterol storage and reduced acidification in endo/lysosomes, consequences of blocking NPC1.…”
Section: Npc1mentioning
confidence: 94%
“…In this review, we focus on the proteins ACE2, TMPRSS2, CTSL, PIKfyve, NPC1, CLTC, EGFR, PPIA, eEF1A, and S100A8. These proteins are of interest because their roles in SARS-CoV-2 infection, replication, or pathogenesis have been well-characterized (e.g., ACE2, TMPRSS2, 24 CTSL, 25 NPC1, 26,27 CLTC, 28 and S100A8 29 ) by cell or animal models, or their inhibitors have shown promising anti-SARS-CoV-2 activities in preclinical studies (e.g., PIKfyve, 12,30 EGFR, 8,31 PPIA, [32][33][34] and eEF1A 11 ). These host proteins can be categorized according to their putative roles in the SARS-CoV-2 life cycle: (a) cell membrane attachment (ACE2), 24 (b) membrane fusion (TMPRSS2), 24 (c) endocytosis (CTSL, 25 PIKfyve, 12,30 NPC1, 26,27 and CLTC 28 ), (d) replication and translation of the viral genome (EGFR, 8,31 PPIA, [32][33][34] and eEF1A 11 ), and (e) immune response (S100A8 29 ; Figure 1).…”
Section: Host Protein Selectionmentioning
confidence: 99%